Bacillus velezensis BVE7 as a promising agent for biocontrol of soybean root rot caused by Fusarium oxysporum - Sun, Lei; Wang, Wei; Zhang, Xue; Gao, Zhongchao; Cai, Shanshan; Wang, Shuang; Li, Yonggang (Frontiers in Microbiology, 2023)
Soybean root rot (SRR), caused by Fusarium oxysporum, is a severe soil-borne disease in soybean production worldwide, which adversely impacts the yield and quality of soybean. The most effective method for managing crop soil-borne diseases and decreasing reliance on chemical fungicides, such as Bacillus spp., is via microbial biocontrol agents. In this study, a soil-isolated strain BVE7 was identified as B. velezensis, exhibiting broad-spectrum activity against various pathogens causing soybean root rot. BVE7 sterile filtrate, at a concentration of 10%, demonstrated significant antifungal activity by inhibiting the conidial germination, production, and mycelial growth of F. oxysporum by 61.11%, 73.44%, and 85.42%, respectively, causing hyphal malformations. The antifungal compound produced by BVE7 demonstrated adaptability to a standard environment. The pot experiment showed that BVE7 suspension could effectively control soybean root rot, with the highest control efficiency of 75.13%. Furthermore, it considerably enhanced the activity of catalase, phenylalanine ammonia lyase, superoxide dismutase, and peroxidase in soybean roots, while also preventing an increase in malondialdehyde activity. By improving the host resistance towards pathogens, the damage caused by fungi and the severity of soybean root rot have been reduced. This study presents the innovative utilization of B. velezensis, isolated from soybean roots in cold conditions, for effectively controlling soybean root rot caused by F. oxysporum. The findings highlight the remarkable regional and adaptive characteristics of this strain, making it an excellent candidate for combating soybean root rot in diverse environments. In conclusion, B. velezensis BVE7 demonstrated potential in effectively reducing SRR incidence and can be considered as a viable option for SRR management.